Laparoscopic excision of accessory cavitated uterine mass and its vaginal retrieval in toto - Kanmani, Mani; Kasthuri, Chinnasamy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Accessory cavitated uterine mass (ACUM), a rare cause of dysmenorrhoea, has to be diagnosed with essential criteria and is to be treated with appropriate surgery. Hereby, presenting the surgical approach by laparoscopy and vaginal retrieval of the specimen in toto as a perfect tool. We report a rare case study of ACUM, a mullerian anomaly in a 27 years old female with severe dysmenorrhoea with secondary infertility, evaluated and diagnosed as ACUM. Preoperative diagnosis and surgical plane evaluation are made by ultrasound and magnetic resonance imaging. Hysteroscopic examination of the cavity was normal and laparoscopic excision of an ill-defined mass in the anterior and right lateral wall of 3×2 cm followed by retrieval of the specimen through a pouch of Douglas. Myometrial defect sutured. Cut section showed chocolate coloured fluid in the endometrial cavity and the same confirmed by histopathology. This is the first case report doing vaginal retrieval of ACUM in toto.